Reforma al artículo 11 de la Ley de Registro - Mora Valencia, José Miguel (2016)
Since the promulgation of the 2008 Constitution, local governments have the authority to manage concurrently with the executive power to property records; which have caused very profound legal effects on the Ecuadorian registration system. As a general rule, the Ecuadorian legislation indicates that any registration process entered to the registration office must be layed down; however, the documentary rating performed by the Registrar might eventually lead to a ruling of refusal or disavowal of the registration. This decision years has been considered as a judicial act for many years, but according with the National Assembly there has been developed the legal system framed in the Constitution; such is that with the promulgation of the Organic Territorial, Organization, Autonomy and Decentralization Code; and the National Service Law of Act Public Data Registry, the registration office becomes an agency that provides a public service; and is in charge by itself of public servant. Consequently annotated, the legal concept of negative registration mutates from a legal act of registration to an administrative act This leads contestation to the registration denial by its nature to become a process that must be known and resolved by the Administrative Court.